การวิเคราะห์ทางเศรษฐศาสตร์ของแรงงานไทยที่เดินทางไปทำงาน ประเทศญี่ปุ่นและประเทศสาธารณรัฐเกาหลี - ปรานสุจริต, เพ็ญวนา; ราษฎร์นิยม, อ้อทิพย์; เพิ่มพูนวิวัฒน์, ชมพูนุท โกสลากร (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2015)
ในการวิจัยเรื่อง การวิเคราะห์ทางเศรษฐศาสตร์ของแรงงานไทยที่เดินทางไปทำงานประเทศญี่ปุ่น และประเทศสาธารณรัฐเกาหลี มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัญหา อุปสรรคจากดำเนินการระหว่าง การเดินทางไปทำงาน และความเป็นอยู่ของแรงงานไทยในในประเทศญี่ปุ่นและประเทศสาธารณรัฐเกาหลี และ 2) คำนวณต้นทุน ผลได้ของแรงงานไทยไปทำงานในประเทศญี่ปุ่นและประเทศสาธารณรัฐเกาหลี ประชากร คือ แรงงานไทยที่เดินทางไปทำงานในประเทศญี่ปุ่นและประเทศสาธารณรัฐเกาหลี โดยกรมการ จัดหางานเป็นผู้จัดส่ง เครื่องมือที่ใช้เป็นแบบสอบถามนำมาวิเคราะห์ข้อมูลโดยใช้ค่าเฉลี่ย ร้อยละ และ การคำนวณมูลค่าปัจจุบันสุทธิ ผลการวิจัย พบว่า ประเทศญี่ปุ่น : แรงงานไทยเกิดปัญหาในการเดินทางเพื่อไปสอบคัดเลือกเพราะสถานที่กำหนดสอบ มีแห่งเดียว การเข้าฝึกอบรมที่ศูนย์พัฒนาฝีมือ มีความกดดันระหว่างฝึกอบรมและอยู่ไกลจากแหล่ง อำนวยความสะดวก ขาดความเข้าใจในสัญญาจ้าง ภาษาญี่ปุ่น นายจ้างละเมิดไม่ปฏิบัติตามสัญญาจ้าง ขาดความรู้ช่องทางสื่อสาร ขอความช่วยเหลือจากหน่วยงานภาครัฐ ไม่สามารถปรับตัวเข้ากับสภาพความ เป็นอยู่ ค่าครองชีพสูง บางราย ถูกชักชวนเข้าบ่อนการพนัน ต้นทุนก่อนเดินทางไปทำงาน 10,711.62 บาท ต้นทุนระหว่างการทำงาน 113,069.19 บาทต่อปี ต้นทุนทางอ้อม 69,729.73 บาทต่อปี ผลได้ส่วนบุคคล 486,810.81 บาทต่อปี และมูลค่าปัจจุบันสุทธิมีค่าเป็นบวก 863,961.04 บาท แสดงว่ามีผลได้มากกว่า ต้นทุน สมควรตัดสินใจเดินทางไปทำงานประเทศญี่ปุ่น ประเทศสาธารณรัฐเกาหลี : แรงงานไทยมีปัญหาในขั้นตอนสมัครสอบ และคัดเลือกจากการได้รับ ข่าวสารจากทางกรมการจัดหางานที่ต้องใช้เวลานาน ขาดความรู้ความเข้าใจกฎหมายแรงงาน ภาษาเกาหลี ตำแหน่งงานไม่ตรงตามที่ระบุในสัญญาจ้าง สภาพความเป็นอยู่ต้องปรับตัว เรียนรู้ภาษา และวัฒนธรรมต่างๆ เป็นเวลานาน ที่พักอาศัยแออัด สาธารณูปโภคไม่ค่อยดี อากาศอุณหภูมิตํ่า ต้นทุนก่อนเดินทางไปทำงาน 43,750.97 บาท ต้นทุนระหว่างการทำงาน 103,009.01 บาทต่อปี ต้นทุนทางอ้อม 62,558.56 บาทต่อปี ผลได้ส่วนบุคคล 379,351.35 บาทต่อปี และมูลค่าปัจจุบันสุทธิมีค่าเป็นบวก 571,326.35 บาท แสดงว่า มีผลได้มากกว่าต้นทุน สมควรตัดสินใจเดินทางไปทำงานประเทศสาธารณรัฐเกาหลี An economic analysis of Thai labor to work in Japan and Republic of Korea The study on an economic analysis of Thai labor to work in Japan and the Republic of Korea aims to 1) explore problems, obstacles of the operation and livelihood of Thai labor force in Japan and the Republic of Korea and 2) calculate cost-benefit for Thai labor in deciding to work in Japan and the Republic of Korea. The people of this study included those Thai labors going to work in Japan and the Republic of Korea. The research instrument was the questionnaire used for collecting data which was then analyzed for mean, percentage and calculated for net present value. Findings from the research indicate that: Japan: Include testing venue as it is designated to only one place, pressure from training at labor development center, labor development center located in the remote area, lack of understanding in employment contract, legal text, Japanese text, breach of employment contract by the employer, lack of knowledge of how to ask for help from the government agency, inability to adapt to new living condition and high living expense and gambling invited by other labors. Direct cost before departing for work of 10,711.62 baht and direct cost for during working in Japan of 113,069.19 baht per year. Indirect cost of 69,729.73 baht per year. Benefit of 486,810.81 baht per year. The net present value is in positive value of 863,961.04 baht. These suggests that going to work in Japan by Thai labor has benefit more than cost and should to decide to go to work in Japan. Republic of Korea: Problems for testing and selection as it took a long time to get news from the Department of Employment, lack of knowledge and understanding in labor laws, Korean language, job available not as stated in the employment contract, adaptation to different social and cultural context, crowded camp, poor facilities and utilities, low temperature. Direct cost before departing for work of 43,750.97 baht and direct cost for during working in Japan of 103,009.01 baht per year. Indirect cost of 62,558.56 baht per year. Benefit of 379,351.35 baht per year. The net present value is in positive value of 571,326.35 baht. These suggests that going to work in Japan by Thai labor has benefit more than cost and should to decide to go to work in the Republic of Korea.